2015
DOI: 10.3389/fneur.2015.00144
|View full text |Cite
|
Sign up to set email alerts
|

Vertigo and Dizziness in the Elderly

Abstract: The prevalence of vertigo and dizziness in people aged more than 60 years reaches 30%, and due to aging of world population, the number of patients is rapidly increasing. The presence of dizziness in the elderly is a strong predictor of falls, which is the leading cause of accidental death in people older than 65 years. Balance disorders in the elderly constitute a major public health problem, and require an adequate diagnosis and management by trained physicians. In the elderly, common causes of vertigo may m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 60 publications
4
85
0
15
Order By: Relevance
“…Several studies have demonstrated that older patients with BPPV have a more protracted course and higher risk of recurrence, but the causes of recurrence are not well understood [2,[4][5][6][7][8]. There are reports that aging contributes to the fragmentation of otoconia, as idiopathic BPPV (iBPPV) is more common in older adults than in younger individuals [8,12].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have demonstrated that older patients with BPPV have a more protracted course and higher risk of recurrence, but the causes of recurrence are not well understood [2,[4][5][6][7][8]. There are reports that aging contributes to the fragmentation of otoconia, as idiopathic BPPV (iBPPV) is more common in older adults than in younger individuals [8,12].…”
Section: Introductionmentioning
confidence: 97%
“…The prevalence of this condition in patients older than 65 years is around 30%, and due to an aging world population, the number of patients is rapidly increasing [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is important not just because of the physical discomfort it causes, but especially because of the consequences that it may generate, such as falls and resulting complications. The presence of dizziness in the elderly is a strong predictor of falls, which is the leading cause of accidental death in people older than 65 years [20].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier study has shown that dizziness is a chronic symptom in older patients, which is closely associated with vestibular disorders. 2 Most importantly, the risk of falling is a significant sequela of vestibular deficits, and the consequences arising from falls might vary and be more serious due to other comorbidities. 3 Furthermore, postural instability and vestibular dysfunction are associated with malnutrition and sarcopenia.…”
Section: Introductionmentioning
confidence: 99%